Teen Victimisation, Survival, and the Formation of Identity in Paro Anand’s The Other: Stories of Difference - Puttaiah, Venkatesh (SARE: Southeast Asian Review of English, 2018)
Paro Anand’s The Other: Stories of Difference (2018) underscores the present-day predicament and challenges that impinge on the lives of Indian teenagers, a theme that is approached cautiously by the author for the benefit of her young adult readers. The narratives, however, are daring in the sense that they focus sharply on the hidden or suppressed, and under-represented, crises faced by youngsters, underlining the urgency of addressing these issues in a society that is still largely ignorant or apathetic. Yet, the literary representation of social malaise, psychological trauma, emotional wretchedness, and physical harm in texts intended primarily for young readers is never an easy task as there is a risk of such texts becoming overtly didactic in their desire to inform and educate. Whether Anand steers clear of this trap – for the stories need to work as stories – is one of the concerns of this essay. Another task of the writer is to depict teenagers as not entirely independent of adults and yet also as not bereft of agency. The essay examines the stories in the collection in relation to the identity formation of the young adult characters, who have to grasp as well as grapple with the complexities – along the axes of gender, class, caste, and disability – of what it means to be growing up in India.